Enzymatic Catalysis in Favor of Blocky Structure and Higher Crystallinity of Poly(Butylene Succinate)-Co-(Dilinoleic Succinate) (PBS-DLS) Copolymers of Variable Segmental Composition - Martyna Sokołowska; Jagoda Nowak-Grzebyta; Ewa Stachowska; Miroslawa El Fray (Materials, 2022)
To systematically investigate the synthesis of poly(butylene succinate)-co-(dilinoleic succinate) (PBS-DLS) copolymers and to enrich the library of polyesters synthesized via a sustainable route, we conducted a two-step polycondensation using fully biobased monomers such as diethyl succinate (DS), 1,4-butanediol (1,4-BD) and dilinoleic diol (DLD) in diphenyl ether, using Candida Antarctica lipase B (CAL-B) as biocatalyst. A series of PBS-DLS copolyesters with a 90-10, 70-30 and 50-50 wt% of hard (PBS) to soft (DLS) segments ratio were compared to their counterparts, which were synthesized using heterogenous titanium dioxide/silicon dioxide (TiO2/SiO2) catalyst. Chemical structure and molecular characteristics of resulting copolymers were assessed using nuclear magnetic spectroscopy (1H- and 13C-NMR) and gel permeation chromatography (GPC), whereas thermal and thermomechanical properties as well as crystallization behavior were investigated by differential scanning microscopy (DSC), dynamic mechanical thermal analysis (DMTA), digital holographic microscopy (DHM) and X-ray diffraction (XRD). The obtained results showed that, depending on the type of catalyst, we can control parameters related to blockiness and crystallinity of copolymers. Materials synthesized using CAL-B catalysts possess more blocky segmental distribution and higher crystallinity in contrast to materials synthesized using heterogenous catalysts, as revealed by DSC, XRD and DHM measurements.